2013
DOI: 10.1186/1757-2215-6-88
|View full text |Cite|
|
Sign up to set email alerts
|

Gene-gene interaction network analysis of ovarian cancer using TCGA data

Abstract: BackgroundThe Cancer Genome Atlas (TCGA) Data portal provides a platform for researchers to search, download, and analysis data generated by TCGA. The objective of this study was to explore the molecular mechanism of ovarian cancer pathogenesis.MethodsMicroarray data of ovarian cancer were downloaded from TCGA database, and Limma package in R language was used to identify the differentially expressed genes (DEGs) between ovarian cancer and normal samples, followed by the function and pathway annotations of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…We suppose that G6PC opens a novel perspective for OvCa treatment, namely targeting glycogenolysis. Nonetheless, unlike the TCGA Renal Cell Carcinoma Project, which identifies metabolic shift as a pivotal abnormality in tumour progression [8], the OvCa consortium has not listed metabolic change as an outstanding finding in their report [5] nor have the subsequent TCGA reproducers identified any significant changes in glucose metabolism in OvCa [20][21][22][23][24][25]. In the pilot stage of the current study, we have also screened expression of genes within glycolytic, PPP, glycogenolytic pathways, etc., and we have found that glycogenolysis is not notably increased in OvCa.…”
Section: Discussionmentioning
confidence: 95%
“…We suppose that G6PC opens a novel perspective for OvCa treatment, namely targeting glycogenolysis. Nonetheless, unlike the TCGA Renal Cell Carcinoma Project, which identifies metabolic shift as a pivotal abnormality in tumour progression [8], the OvCa consortium has not listed metabolic change as an outstanding finding in their report [5] nor have the subsequent TCGA reproducers identified any significant changes in glucose metabolism in OvCa [20][21][22][23][24][25]. In the pilot stage of the current study, we have also screened expression of genes within glycolytic, PPP, glycogenolytic pathways, etc., and we have found that glycogenolysis is not notably increased in OvCa.…”
Section: Discussionmentioning
confidence: 95%
“…FOXM1 expression can also be induced by other mechanisms including (i) increased transcription through the action of transcription factors E2F, c-Myc, and hypoxia-inducible factor-1 (HIF-1) [13][14][15]; (ii) loss transcription repression due to mutations in the tumor suppressor p53 (seen in approximately half of HCC patients) [16][17][18] and (iii) decreased expression of microRNAs (miRNAs) such as miR-149 and miR-134 which down-regulate FOXM1 post-transcriptionally [19,20]. Bioinformatic analyses of genome-wide transcriptional sequencing data in HCC have identified alterations of the FOXM1 transcription network including downstream FOXM1 effectors AURKB, BIRC5, CCNB1, CCNB2 and NEK2 [21,22].…”
Section: Pi3k/akt Pathway Is Involved In the Sorafenib Resistancementioning
confidence: 99%
“…7 GSTM1 gene polymorphism can change the ability of the enzymes' activation or deactivation of the heterologous substrate, which can affect individual susceptibility to lung cancer after exposure. [8][9][10][11] Previous studies somehow identified the functional role of CYP2E1 or GSTM1 polymorphism and lung cancer risk; several studies also showed the synergistic interaction between gene polymorphisms and environmental cancerogens, 12 and gene-gene interaction among metabolic enzyme genes, 13,14 but interactions between CYP2E1 and GSTM1 polymorphism, these polymorphisms and environmental factors have seldom been reported, 15 and the results of these studies are not consistent. Besides, lung cancer ranks the first both in incidence and mortality rates of cancer in Zhejiang Province in recent years.…”
Section: C-t Replacement In 5′ Regulatory Region Studies Show That Tmentioning
confidence: 99%